Symbiotic Relationships in Octocorals: The Role of Gorgonians - Cuecuecha-Pérez, Linda Flor; Ávila-García, Ariadna Esmeralda (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sumDO - 10.30878/ces.v32n0a27, 2025)
Octocorals are structurally complex organisms with significant ecological importance. Their morphology allows them to create multiple habitats, promoting their association with other marine species and thereby increasing ecosystem biodiversity. These interactions can be classified as symbiotic relationships or associations with fauna. Symbiotic relationships, being more specialized, can be categorized based on their impact on the host and the duration of the symbiosis, differentiating among three main types: mutualism, commensalism and parasitism. This article aims to highlight the role of octocorals in interspecific relationships within an ecosystem, as well as to emphasize their diversity and importance. Currently, organisms from seven phyla have been recorded inhabiting octocorals; therefore, studies that classify these interactions or utilize non-invasive methodologies for their study are lacking.